FUNDAMENTAL DIFFERENCES BETWEEN CONVENTIONAL BANKS AND SHARIA BANKS AS SEEN FROM THE PERSPECTIVE OF ISLAMIC LAW - Dedy Felandry (Proceeding International Conference on Social Sciences, 2026)
The purpose of this research is to analize and to understand the fundamentals difference between conventional banks and syariah banks reviewed from perspective of Islamic economy law, to be able to contribute to the state as an arranger, coach, and supervisor, and the one who make regulation in Indonesian would of banking. The result of this research can be used as a basic step in running the fuction of the state as an arranger, coach, and supervisor, and the one who make regulation in Indonesian would of banking. Beside that, the formulation can be useful for the policy maker in drafting regulation and other policys. Specific target of this research is to formulate regulation drafting to create the world of syariah banking that essentially to the Islamic syariah. And the result can be used as evaluation of consistence between syariah banking idealism in normative and how if carried in fact. The method of this research is normative legal research, also known as library legal research, which is a method that used in legal research by researching in library’s substances. Data resource in this research is : Primary legal research, wich is legal substance from the regulations Secondary legal research, wich came from literature, books, journals, and legal expert opinions. Tertier legal research, which used to support the primary and secondary legal resource like dictionary and encyclopedia.